Microtensile bond strength between self-adhesive resin cements and resin based ceramic CAD/CAM block = Resistencia adhesiva microtensil entre cementos de resina autoadhesivos y bloques de cerámica CAD/CAM a base de resina - Berkman, Meriç
Purpose: The objective of this study is to evaluate and compare the microtensile bond strength (μTBS) of four different self-adhesive resin cements to a resin-based ceramic CAD/CAM block, at the baseline, and after subjecting them to 5,000 thermo-cycles.Materials and Methods: Four self-adhesive dual-cured resin cements; G-CEM LinkAce (GC EUROPE, Leuven, Belgium), RelyX U200 (3M ESPE, Seefeld, Germany), Maxcem Elite (Kerr, CA, USA), TheraCem (Bisco, Schaumburg, USA) were applied to Cerasmart CAD/CAM blocks (GC EUROPE, Leuven, Belgium). CAD/CAM blocks were sectioned into sticks and subjected to μTBS tests at 24 hours, and the other half were subjected to tests after 5000 thermo-cycles. The data were tested by one-way variance analysis (p<0.05). Results: The highest bond strength values were observed in TheraCem, followed by G-CEM LinkAce and RelyX U200, respectively (p<0.05). At the baseline, G-CEM LinkAce, RelyX U200, and Maxcem Elite showed statistically similar results. After 5,000 thermal-cycles, a significant decrease was observed in the bond strength values of G-CEM LinkAce (p<0.05). Conclusion: Between the adhesive cements used in the study, TheraCem showed the highest micro-tensile bond strength values both in the baseline (24h) results, and after the 5,000 thermal-cycle aging procedures.